2003
DOI: 10.1177/0739986303256913
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Youth of the Southwest Borderlands: Perceptions of Ethnicity, Acculturation, and Race

Abstract: This article discusses the findings of a qualitative study of a group of young Mexican Americans in a barrio, fictitiously called “Las Montañas Bonitas,” located in a large Southwestern city. Young Mexican Americans’perception of ethnic identity is the focus of this study. The ethnographic techniques of participant observation, focus groups, and semistructured interviews were used. The most poignant finding is the respondents’use of racial terms to define and understand acculturation differences. Also, the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Other studies underscored the need for researchers to understand what it means to be a member of an ethnically distinct group before attempting to develop prevention messages for members of those groups (Marsiglia, Miles, Dustman, & Sills, 2002;Napoli, Marsiglia, & Kulis, 2003;Okamoto, Hurdle, & Marsiglia, 2002;Sheets, 2003). Because no evidence-based research had been done with, by, and for adolescents from nondominant groups (Gosin, Dustman, Drapeau, & Harthun, 2003;Schinke, Botvin, & Orlandi, 1991) at the time this project was undertaken, the so-called culturally neutral messages of universal substance abuse prevention efforts ignored the contributions and needs of those students (Holleran, 2003;Hurdle, Okamoto, & Miles, 2002;Marsiglia et al, 2001).…”
Section: Project Foundationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies underscored the need for researchers to understand what it means to be a member of an ethnically distinct group before attempting to develop prevention messages for members of those groups (Marsiglia, Miles, Dustman, & Sills, 2002;Napoli, Marsiglia, & Kulis, 2003;Okamoto, Hurdle, & Marsiglia, 2002;Sheets, 2003). Because no evidence-based research had been done with, by, and for adolescents from nondominant groups (Gosin, Dustman, Drapeau, & Harthun, 2003;Schinke, Botvin, & Orlandi, 1991) at the time this project was undertaken, the so-called culturally neutral messages of universal substance abuse prevention efforts ignored the contributions and needs of those students (Holleran, 2003;Hurdle, Okamoto, & Miles, 2002;Marsiglia et al, 2001).…”
Section: Project Foundationsmentioning
confidence: 97%
“…Because narratives are linked to membership in speech communities (Holleran, 2003;Nikitina, 2003), language provided an arena in which actions were justified by citing reasons that were meaningful to community members.…”
Section: Culturally Grounded Prevention Messagesmentioning
confidence: 99%
“…Chavez-Dueñas et al, 2014;Holleran, 2003). Research has demonstrated that, to date, Latinos/as with darker complexions and indigenous features still have fewer social achievements and experience more discrimination than lighter counterparts (cf.…”
Section: Colorismmentioning
confidence: 99%
“…Latino adults use national origin most often as a marker for self-identification (Latino National Political Survey, cited in Schmidt, Barvosa-Carter, & Torres, 2000). Second-generation Latino youths, however, tend to see their ethnicity in racial terms (Portes & Rumbaut, 2001), perhaps because the selection of a label may be influenced by how others perceive youths (Brunsma & Rockquemore, 2001) and because the dominant U.S. culture uses race as a way of understanding ethnic differences (Holleran, 2003). Applied to this study, youths who are less acculturated to the U.S. ideology would select only a Mexican/Mexican American/Chicano label.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In such an environment, people who are U.S.-born —particularly white people—often create and accept negative stereotypes about Mexican-origin communities and talk derogatorily about “Mexicans” (Holleran, 2003). Massey and Denton (1992) asserted that experiencing discrimination reinforces a racially distinct identity among Mexican immigrants when they realize that “they will not be accepted as whites” (p. 240).…”
Section: Theoretical Frameworkmentioning
confidence: 99%